The effect of dentures on oral health and the quality of life - Jar, Alabbas A.; Khormi, Abdullah A.; Al-khamiss, Norah A.; Alnaim, Atheer A.; Alharbi, Zainab F.; Holba, Hesham A.; Alshamrani, Abdullah S.; Khormi, Anwer A.; Alharbi, Amani S.; Almutairi, Arwa M.; Alhegbani, Faisal A. (International Journal Of Community Medicine And Public Health, 2023)
Dentures, as versatile dental prostheses, wield a multifaceted influence on individuals' lives, profoundly affecting both their oral health and overall quality of life. The clinical manifestations of denture-related concerns encompass a spectrum of physical, psychological, and functional dimensions. Physically, dentures restore masticatory function and address aesthetic concerns, bridging the gap between tooth loss and oral functionality. Psychologically, they elevate self-esteem and reduce social anxiety, facilitating enhanced self-confidence and improved social interactions. Functionally, dentures enhance articulation and speech clarity, enabling effective communication. Effective denture management, in the contemporary landscape of dental care, involves a comprehensive approach that combines precision, technology, hygiene, and patient education. Digital dentistry techniques ensure precise denture fitting, and advanced technologies facilitate regular check-ups, leading to well-fitting, comfortable dentures. Meticulous denture hygiene practices prevent oral health complications. Patient education empowers individuals to maintain their oral health effectively, while addressing psychosocial concerns remains a crucial empathetic dimension of patient care. In conclusion, dentures have evolved as transformative solutions for individuals facing tooth loss, addressing clinical manifestations related to impaired oral function, aesthetic concerns, and psychosocial challenges. Modern denture management embraces the latest dental technologies, hygiene practices, and patient-centered approaches to optimize outcomes. Staying current with advancements in denture care ensures that these dental prostheses continue to enhance oral health and overall well-being effectively, reaffirming their indispensable role in modern dentistry.